2019
DOI: 10.1016/j.cortex.2018.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Language lateralisation measured across linguistic and national boundaries

Abstract: The visual half-field technique has been shown to be a reliable and valid neuropsychological measurement of language lateralisation, typically showing higher accuracy and faster correct responses for linguistic stimuli presented in the right visual field (RVF) than left visual field (LVF). The RVF advantage corresponds to the well-known dominance of the left hemisphere (LH) in processing language(s). However, clinical and experimental neuroscientists around the globe use different variations of the visual half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 72 publications
9
25
0
Order By: Relevance
“…With 100 participants completing 256 trials, Willemin et al reported a RVF advantage at the population level. Since then this effect has been replicated in a sample of 496 participants covering six international languages, with evidence of a RVF for each language studied (Hausmann et al, 2019). Not only does this task show validity, it seems reliable given Brederoo et al's (2020) observation that the task yields good split-half reliability when tested with 122 participants: r = 0.86 for error rates and r = 0.80 for response times.…”
Section: Lateralized Visual Word Processingmentioning
confidence: 80%
See 1 more Smart Citation
“…With 100 participants completing 256 trials, Willemin et al reported a RVF advantage at the population level. Since then this effect has been replicated in a sample of 496 participants covering six international languages, with evidence of a RVF for each language studied (Hausmann et al, 2019). Not only does this task show validity, it seems reliable given Brederoo et al's (2020) observation that the task yields good split-half reliability when tested with 122 participants: r = 0.86 for error rates and r = 0.80 for response times.…”
Section: Lateralized Visual Word Processingmentioning
confidence: 80%
“…Our task was designed to require covert speech, raising the question of whether an active speech production component might reveal stronger lateralization. However, this explanation seems unlikely, given that recent studies have reported robust right visual-field advantages on a lexical decision task that does not require active speech production (Brederoo et al, 2020;Hausmann et al, 2019;Willemin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Having said that, these tasks are easy to set up and administer. In fact, the kind of large numbers required for our proportional analyses lend themselves rather nicely to a multi-lab approach which for example, has been recently used to great effect in examining visual half field studies of lexical decision (Hausmann et al, 2019). We submit that behavioural psychology can contribute substantially to such taxonomic efforts, in ways that expensive, time constrained, brain scans cannot.…”
Section: Discussionmentioning
confidence: 98%
“…Surprisingly, of 13 tasks employed, for 8 the correlations were negative, precluding the generalization that performance increases with lateralization. Other studies diverge too: some report a positive relation (Crow, Crow, Done, & Leask, 1998;Mellet et al 2014;Hirnstein, Hausmann, & Hugdahl, 2014), some a negative relation (Ladavas & Umilta, 1983;Hirnstein, Hausmann, & Gunturkun, 2008;Hausmann et al, 2019), and some no relation between asymmetry and performance at all . Chiarello, Welcome, Halderman and Leonard (2009) and Chiarello, Vazquez, Felton, and Leonard (2013) found a positive relation between asymmetry and performance in lexical processing, but only in individuals with consistent hand preference.…”
Section: Is Laterality Adaptive?mentioning
confidence: 99%